Antifungal Susceptibility and Candida sp. Biofilm Production in Clinical Isolates of HIV-Positive Brazilian Patients under HAART Therapy - Anelise Maria Costa Vasconcelos Alves; Érika Helena Salles de Brito; Márcio Flávio Moura de Araújo; Juliana Jales de Hollanda Celestino; Ana Caroline Rocha de Melo Leite; Gabriela Silva Cruz; Nuno Filipe Azevedo; Célia Fortuna Rodrigues (Biomedicines, 2024)
The aim of the present study was to characterize biofilms formed by Candida spp. clinical isolates (n = 19), isolated from the oral mucosa of HIV-positive patients. For characterizing the biofilms formed by several Candida sp. strains, isolated from HIV-positive patients, in terms of formed biomass, matrix composition and antifungal susceptibility profile, clinical isolates (n = 19) were collected from oral mucosa and identified. The biofilm of the samples was cultured with fluconazole (1250 mg/L), voriconazole (800 mg/L), anidulafungin (2 mg/L) or amphotericin B (2 mg/L). Afterwards, the quantification of the total biomass was performed using crystal violet assay, while the proteins and carbohydrates levels were quantified in the matrix. The results showed a predominance of C. albicans, followed by C. krusei. Around 58% of the Candida spp. biofilm had susceptibility to fluconazole and voriconazole (800 mg/L), 53% to anidulafungin and 74% to amphotericin B. C. krusei presented both the lowest and the highest biofilm matrix contents in polysaccharides and proteins. The low resistance to antifungal agents reported here was probably due to the fact that none of the participants had a prolonged exposure to these antifungals. A predominance of less virulent Candida spp. strains with low or no resistance to antifungals was observed. This can be attributed to a low fungal selective pressure. This most probably happened due to a low fungal selective pressure but also due to a good adherence to HAART therapy, which guarantees a stable and stronger immune patient response.